Pengaruh Tunjangan Kinerja Dan Jaminan Sosial Terhadap Kinerja Pegawai Pada Dinas Sumber Daya Air, Cipta Karya Dan Tata Ruang Provinsi Sumatera Utara - Erni Yusnita Sari; Indra Utama (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
This study aims to determine: (1) The effect of performance allowances on employee performance at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province. (2) The effect of social security on employee performance at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province. (3) The effect of performance allowances and social security on employee performance at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province.This type of research is descriptive quantitative research. The population in this study was 60 employees. Samples were managed using saturated sampling, namely taking the entire population to be used as samples so that the sample in this study was 60 respondents. Data collection techniques use the method of observation, interviews, and questionnaires. The data analysis technique in this research is Multiple Linear Regression.Based on the results of this study are as follows: (1) Performance allowances have a positive and significant effect on employee performance at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province as indicated by the value of tcount (2.161) > ttable (1.672). (2) Social security has a positive and significant effect on the performance of employees at the Department of Water Resources, Cipta Karya and Spatial Planning of North Sumatra Province as indicated by the value of tcount (2.103) > t table (1.672). (3) Performance allowances and social security simultaneously affect the performance of employees at the Department of Water Resources, Creation and Spatial Planning of North Sumatra Province as indicated by the value of Fcount > Ftable (6.448 > 3.16). Keywords: Allowance, Performance, Social. Security, Employee